A Stereoselective Approach to Functionalized Cyclohexenones. Issue 31 (13th September 2013) - Meister, Anne C.; Sauter, Paul F.; Bräse, Stefan
Abstract: A catalytic enantioselective approach to 4‐hydroxy‐6‐methylcyclohex‐2‐enones is presented herein. The stereogenic information is generated through a copper‐catalyzed 1, 4‐addition to p ‐benzoquinone monoketal using a chiral, BINOL‐based (BINOL = 1, 1′‐bi‐2‐naphthol) phosphane ligand, according to the procedure of Feringa et al. A CBS (Corey–Bakshi–Shibata) reduction of the 1, 4‐adducts gave the four possible isomers in two steps and 82–97 %  ee (enantiomeric excess), starting from commercially available 4, 4‐dimethoxycyclohexa‐2, 5‐dien‐1‐one (7 ). Abstract : A stereoselective approach to the natural product building block 4‐hydroxy‐6‐methylcyclohex‐2‐enone is presented herein. Four different isomers were obtained with excellent enantiomeric excess values and good diastereoselectivities through a two‐step process that started from 4, 4‐dimethoxycyclohexa‐2, 5‐dien‐1‐one. This represents the shortest synthetic approach to these molecules.